Entering new markets and diversifying business: The role of Amazon's acquisitions in international growth and development - Stefan Schmid; Sebastian Baldermann (ESCP Europe Wirtschaftshochschule Berlin, 2019)
E-commerce has grown considerably in recent decades and has had a disruptive impact on the retail industry. In this context, Amazon, one of the major players in (online) retailing and beyond, has been able to expand its business activities continuously in many countries. The present case study sheds light on the internationalization of Amazon, with a particular focus on the company's acquisitions. The study illustrates that Amazon's acquisitions over the last decades had two major objectives. First, acquisitions helped Amazon enter new markets and strengthen its presence in specific regions. Second, taking over other companies allowed Amazon to broaden its activities, for instance, by expanding the product portfolio, improving customer service, gaining additional knowledge and expertise or by opening up new business areas.
Keywords: 650; Acquisition; Amazon; Case Study; Diversification; E-Commerce; Infrastructure; International Expansion; Internationalization; Internet; Logistics; Market Entry; Online; Platform; Product Innovation; Retailing; Technology; United Arab Emirates; Web Services